Influence of the program "tocando construyo" in the development of geometric skills in children of the 2nd grade of Los Olivos - Mamani Choquetico, Maribel (2018)
The research was developed in an experimental design at a quasi-experimental level with pre- and post-test measurement, in two groups of previously trained subjects, with the objective of determining the influence of the Tocando Construyo Program on the development of geometric skills in children of the 2nd grade of primary, relying on the hypothetical deductive method. The sample was formed by two groups: section B (28 students) and section D (28 students). The data collection was done through the application of the evaluation test. The results obtained allowed us to conclude that the application of the Tocando Construyo Program favorably influenced the development of geometric skills in children in the 2nd grade of primary school.